Isolation and Characterization of Primary Retinal Microglia From the Human Post-mortem Eyes for Future Studies of Ocular Diseases - Wang, Luoziyi; Qian, Yiwen; Che, Xin; Jiang, Jing; Suo, Jinshan; Wang, Zhiliang (Frontiers in Cellular Neuroscience, 2022)
Microglia, the primary resident immunocytes in the retina, continuously function as immune system supervisors in sustaining intraocular homeostasis. Microglia relate to many diseases such as diabetic retinopathy, glaucoma, and optic nerve injury. To further investigate their morphology and functions in vitro, a reliable culture procedure of primary human retinal microglia is necessary. However, the culture condition of microglia from the adult retina is unclear. Researchers created several protocols, but most of them were carried out on rodents and newborns. This study described a protocol to isolate and characterize human primary retinal microglia from human post-mortem eyes. The whole procedure started with removing retinal vessels, mechanical separation and enzymatic dissociation, filtration, and centrifugation. Then we cultured the cell suspensions on a T-75 flask for 18 days and then shook retinal microglia from other retinal cells. We found numerous retinal microglia grow and attach to Müller cells 10 days after seeding and increase rapidly on days 14-18. Iba1 and P2RY12 were used to qualify microglia through immunofluorescence. Moreover, CD11b and P2RY12 were positive in flow cytometry which helps to discriminate microglia from other cells and macrophages. We also observed a robust response of retinal microglia in LPS treatment with proinflammatory cytokines. In conclusion, this study provides an effective way to isolate and culture retinal microglia from adult human eyes, which may be critical for future functional investigations.